2021
DOI: 10.3892/ijo.2021.5231
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA NEAT1 facilitates the progression of colorectal cancer via the KDM5A/Cul4A and Wnt signaling pathway

Abstract: Colorectal cancer (CRC) is a major cause of cancer-related mortality. The aberrant expression of long non-coding RNAs (lncRNAs) is implicated in the pathogenesis of CRC. The present study investigated the role of lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) in CRC. lncRNA NEAT1 expression was detected in CRC tissues and cell lines. HCT116 cells were transfected with si-NEAT1, and the malignant behavior of the cells was detected. The binding associations between NEAT1 and E2F1, as well as between E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…GSEA indicated that the differential genes grouped according to SLC2A1 expression were primarily participated in REACTOME G ALPHA I SIGNALING EVENTS, REACTOME M PHASE, REACTOME NEURONAL SYSTEM, WP LNCRNA INVOLVEMENT IN CANONICAL WNT SIGNALING AND COLORECTAL CANCER, PID HIF1 TFPATHWAY, and REACTOME GLYCOLYSIS pathways. According to previous research studies, we found that the progression and metastasis of CRC are significantly correlated to the latter three pathways ( Peng et al, 2020 ; Shen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 54%
“…GSEA indicated that the differential genes grouped according to SLC2A1 expression were primarily participated in REACTOME G ALPHA I SIGNALING EVENTS, REACTOME M PHASE, REACTOME NEURONAL SYSTEM, WP LNCRNA INVOLVEMENT IN CANONICAL WNT SIGNALING AND COLORECTAL CANCER, PID HIF1 TFPATHWAY, and REACTOME GLYCOLYSIS pathways. According to previous research studies, we found that the progression and metastasis of CRC are significantly correlated to the latter three pathways ( Peng et al, 2020 ; Shen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 54%
“…NEAT1 has been previously shown to be associated with CRC through several mechanisms of action. NEAT1 is responsible for indirect activation of the Wnt/β‐catenin signaling pathway via binding to DDX5 and KDM5A/Cul4A/Wnt axis 26,82 . In addition, NEAT1 regulates several tumorigenesis‐associated pathways via sponging multiple miRNAs 83 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed critical roles of Lnc-NEAT1 in a variety of cancers. For instance, Fan et al [ 26 ] demonstrated that cancer-related fibroblasts-secreted exosomal Lnc-NEAT1 promoted endometrial cancer development through upregulating miR-26a/b-5p-targeted STAT3 signaling pathway, and Shen et al [ 27 ] testified that lncRNA NEAT1 stimulated malignant behaviors of colorectal cancer through mediating KDM5A/Cul4A and Wnt pathways. Noticeably, consistent with these reports, our findings further validated the oncogenic role of Lnc-NEAT1 in LP.…”
Section: Discussionmentioning
confidence: 99%